PICTURE SERIES TRIGGERING MEMORY RETRIEVAL OF A STORY AS REPRESENTED IN WRITING NARRATION - Maria Crystina Napitupulu; Berlin Sibarani; I Wayan Dirgeyasa (Universitas Negeri Medan, 2019)
The aims of this study is to analyze picture series trigger memory retrieval of a story as represented in writing narration. This study was conducted by using descriptive qualitative design. The source of this data are the students of SMA Swasta Kartika Medan which consists of 18 students. To collect the data, elicitation technique was used in this study. To elicit the students writing, picture series of different completeness will be presented to the students. There are three concurrent flows of action to analyze the data, they are data condensation, data display, and conclusion drawing/ verification. After analyzing the data, the researcher found that the way how picture series trigger memory retrieval is that by suiting the number of clues presented to the background knowledge of the writers. The more the background knowledge of the writers have, the less clues they need to trigger memory retrieval. On the other hand, the less the background knowledge of the writers have, the more clues they need to trigger memory retrieval. Key words : Picture series, Triggering, Memory Retrieval, Writing Narration.